(untitled) (Global Journal of Management and Business Research, 2021)
For the better part of the last twenty years, a multitude of international conventions, principles, standards have been agreed to strengthen governance and reduce corruption. These have led to a plethora of statements, institutions and regulations, experiments - each with their own valid inner logic. However, if we look for tangible, on-the-ground results, we are in for a big surprise, or rather disappointment.